The essential properties governing the appropriate selection of phase change materials integrated into heavy structure buildings. (1st March 2023) - El-Raheim, D. Abd; Mohamed, A.; Abou-Ziyan, H.; Fatouh, M.
Abstract: This paper examines the essential properties governing the appropriate selection of phase change materials (PCMs) integrated into heavy structure buildings during different seasons. Nine PCMs with various thermophysical properties were evaluated, in the free-floating mode, under hot and dry climate conditions. The practical examined range of each property is extracted from the data of the nine considered PCMs. An indoor experiment was designed and constructed to validate the simulation models created with the EnergyPlus and Designbuilder building simulation programs. The results confirm that the large latent heat of fusion and low thermal conductivity of PCMs enhance the indoor thermal comfort at the same melting temperature. The Intensity of Thermal Discomfort (ITD) decreases from 51 to 36.4% as the energy density increases from 138.6 to 180.6 MJ/m 3, for two PCMs with a melting temperature of 21 °C. As the PCM melting temperature increased from 21 to 29 °C, the ITD index decreased from 27 to 10 °C.day. Thus, the occupants' thermal comfort enhances as the PCM melting temperature approaches the upper limit of the adaptive thermal comfort. In brief, the ITD sensitivity index (the relative change in ITD due to a relative change in PCM property) is highly affected by the PCM melting temperature (5.85), followed by latent heat (1.37), density (0.71), thermal conductivity (0.41), and the phase transition region (0.096) that has a negligible effect on the indoor thermal comfort. Highlights: Phase change materials integrated into buildings are valuable in free-floating mode. Properties governing the proper selection of phase change materials are identified. Melting temperature is the dominant property affecting thermal comfort in buildings. High latent heat and low thermal conductivity enhance thermal comfort in buildings. Selection of material based on the melting temperature only is not a proper choice.